2021
DOI: 10.1111/conl.12843
|View full text |Cite
|
Sign up to set email alerts
|

Village modernization may contribute more to farmland bird declines than agricultural intensification

Abstract: The central tenet of European farmland ecology is that agricultural intensification during the 20th century was largely responsible for dramatic declines in species abundances. However, during this time, human rural settlements were also undergoing radical changes through modernization, with undocumented biodiversity impacts in this important wildlife habitat. We performed the first ever large‐scale study to disentangle the impact of these simultaneous processes on farmland bird diversity in 104 Polish village… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 33 publications
(66 reference statements)
1
14
0
1
Order By: Relevance
“…We agree with Rosin et al. (2021) that village modernization might be an important driver of farmland species declines, and that maintaining wildlife‐friendly infrastructures is a potential lever to restore depleted populations. However, certain elements in this study are potential sources of confusion for the unwary reader and might result in a misinterpretation of the conclusions by practitioners and policy‐makers.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…We agree with Rosin et al. (2021) that village modernization might be an important driver of farmland species declines, and that maintaining wildlife‐friendly infrastructures is a potential lever to restore depleted populations. However, certain elements in this study are potential sources of confusion for the unwary reader and might result in a misinterpretation of the conclusions by practitioners and policy‐makers.…”
supporting
confidence: 92%
“…Rosin et al. (2021) draw the attention of the conservation community toward the impact of village modernization on farmland bird populations. Village modernization affects synanthropic farmland biodiversity through a loss of nesting and foraging habitat (Rosin et al., 2016).…”
mentioning
confidence: 99%
“…Increasing evidence shows that rural villages and especially farmsteads may represent crucial habitats for farmland birds, with farmsteads harbouring higher abundance and species diversity than surrounding farmed and semi-natural habitats (Hiron et al, 2013;Rosin et al, 2016Rosin et al, , 2021Šálek, Bažant, et al, 2018). Especially in Central and Eastern European countries (CEECs), traditional rural settlements and farmsteads are an integral part of rural agricultural landscapes.…”
Section: Introductionmentioning
confidence: 99%
“…barn swallow Hirundo rustica , house martin Delichon urbica and house sparrow Passer domesticus ) have substantially declined in recent decades, becoming of conservation concern in many European regions (Ambrosini et al, 2002; Hole et al, 2002). Rosin et al (2021) demonstrated that village modernization in Poland contributed far more to farmland bird population declines than agricultural intensification. Similarly, they found that old farmsteads hosted a higher number of species and individuals than new ones (Rosin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In their reply to Rosin et al (2021), Hertzog et al (2022), while generally agreeing that village modernization (VM) may be an overlooked driver of variation in farmland bird abundances, raise three issues of criticism: (1) an inappropriate space-for-time substitution was used for predicting declines, (2) the abundance of field nesting birds could be driven by a factor other than VM, and (3) our discussion of relevant EU programs for conservation measures targeted on rural buildings was too narrow.…”
mentioning
confidence: 99%